Typification of Centaurea gentilii (Asteraceae) - Ferrer-Gallego, Pedro Pablo; Merle, Hugo; Laguna, Emilio (Phytotaxa, 2018)
The typification of the name Centaurea gentilii (Asteraceae) is discussed. A lectotype collected in Essaouira (Morocco) by Braun-Blanquet in 1921 and preserved in the “Herbier de l’Université Montpellier II” (MPU) is designated as the lectotype.